MENINGKATKAN REGULASI EMOSI MAHASISWA DALAM MENGENDALIKAN PERILAKU AGRESIF MELALUI PELATIHAN MEDITASI MINDFULLNESS - Joko Krisdiyanto (Program Studi Psikologi Universitas Malahayati, 2022)
ABSTRACT: IMPROVING STUDENT EMOTION REGULATION IN CONTROLLING AGRESSIVE BEHAVIOR THROUGH MINDFULLNESS MEDITATION TRAINING This research aimed to look at the effects of mindfulness meditation training on emotion regulation students with aggressive behavior. This research provides a mindfulness meditation training to the experimental group and the control group did not receive treatment. Respondents of each experimental group and control group were 50 respondents who had a low score of emotional regulation and a high score of aggressiveness. The emotional regulation of the respondents in this study was measured using a scale of emotion regulation. Answering the hypothesis, there is an effect of mindfulness meditation on emotion regulation, data analysis was carried out using the Independent Sample T-test technique, and the results showed that there were differences in the emotional regulation scores of the group receiving mindfulness meditation (M=18.2, SD=1.25) and the emotional regulation score of the group receiving mindfulness meditation. did not get mindfulness meditation (M=10.4, SD= .57; t (48)= 5.004, p = .001). Mindfulness meditation training has an effect on increasing the emotional regulation of students with aggressive behavior, so mindfulness meditation can be an alternative to improve emotion regulation. Keywords: Aggressive Behavior, College Student, Emotion Regulation, Mindfulness Meditation Penelitian ini bertujuan untuk melihat pengaruh pelatihan meditasi mindfulness terhadap regulasi emosi mahasiswa dengan perilaku agresif. Penelitian ini memberikan pelatihan meditasi mindfulness kepada kelompok eksperimen sedangkan kelompok kontrol tidak mendapatkan perlakuan. Responden masing-masing kelompok eksperimen dan kelompokkontrokadalah 50 orang responden yang mempunyai skorregulasiemosirendah dan skor agresivitas tinggi. Regulasi emosi Responden penelitian ini diukur dengan menggunakan skala regulasi emosi. Menjawab hipotesis, ada pengaruh meditasi mindfulness terhadap regulasi emosi, dilakukan analisis data menggunakan teknik Independent Sample T-test, dan diperoleh hasil ada perbedaan skor regulasi emosi kelompok yang memperoleh meditasi mindfulness (M=18.2, SD=1.25) dan skor regulasi emosi kolompok yang tidak mendapatkan meditasi mindfulness (M=10.4, SD=.57; t (48)= 5.004, p = .001). Pelatihan meditasi mindfulness berpengaruh dalam meningkatkan regulasi emosi mahasiswa dengan perilaku agresif, sehingga meditasi mindfulness bisa menjadi alternatif untuk meningkatkan regulasi emosi. Kata Kunci: Perilaku Agresi, Mahasiswa, Regulasi Emosi, Meditasi Mindfulness